2016
DOI: 10.1002/cctc.201600184
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Tungsten Nitride and Palladium for the Selective Hydrogenation of Cinnamaldehyde at the C=C bond

Abstract: Herein, a series of catalysts made of Pd–WN on various supports was synthesized by modifying supports with small‐size WN NPs firstly and loading Pd subsequently. Their catalytic performances were evaluated for selective hydrogenation of cinnamaldehyde (CAL) to hydrocinnamaldehyde (HALD). Interestingly, it was found the synergistic effect between Pd and WN can improve conversion and selectivity of CAL to HALD. Among these catalysts, Pd–WN/SBA‐15 shows best performance with highest conversion (99 %) and selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Therefore, it indicates that both the high conversion of CAL and excellent selectivity to HALD over the 0.2%Pd-x%Ni/SBA-15 catalysts were caused by the high amount of the surface Pd 0 . This is in keeping with our previous studies where a large number of surface Pd 0 species enhanced the hydrogenation activity of the substrates [7,9,58]. Table S2 summarizes the selective hydrogenation of CAL over the Pd-based catalysts reported from the literature.…”
Section: Hydrogenation Of Cal To Hald Over Pd-ni/sba-15supporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, it indicates that both the high conversion of CAL and excellent selectivity to HALD over the 0.2%Pd-x%Ni/SBA-15 catalysts were caused by the high amount of the surface Pd 0 . This is in keeping with our previous studies where a large number of surface Pd 0 species enhanced the hydrogenation activity of the substrates [7,9,58]. Table S2 summarizes the selective hydrogenation of CAL over the Pd-based catalysts reported from the literature.…”
Section: Hydrogenation Of Cal To Hald Over Pd-ni/sba-15supporting
confidence: 86%
“…In addition, the Pd-WN/SBA-15 samples were synthesized, and the results indicated that the addition of WN could lead to greatly enhanced performance and good reusability for the ternary Pd-WN/SBA-15 catalyst. This improvement was assigned to the strong interaction of Pd and WN leading to an increase in the ratio of surface Pd 0 species as well as a decrease in the Pd particle size on the SBA-15 supported Pd-WN catalyst [9].…”
Section: Scheme 1 Reaction Routes For the Hydrogenation Of Cinnamaldmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure displays the XPS results of Pd/SiC, Ir/SiC and PdIr/SiC (XPS spectra of other Pd‐Ir bimetallic catalysts are shown in Figure S2). For Pd/SiC, the peaks at 335.64 and 340.96 eV are ascribed to Pd 0 , and the peaks at 336.39 and 341.88 eV correspond to Pd 2+ species . For PdIr/SiC catalyst, however, all of these peaks shift toward higher binding energies, 335.84 and 341.14 eV for Pd 0 , 336.68 and 342.17 eV for Pd 2+ , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…To further improve the performance of Pd‐based catalysts, different additives are usually applied. For example, Fu's group reported that the addition of tungsten nitridecan obviously improves the activity and selectivity of Pd/SBA‐15 for CAL hydrogenation to HALD . Besides, addition of a secondary metal component has also exhibited a promising potential to optimize the catalytic performance via potential synergistic effects between two metals .…”
Section: Background and Originality Contentmentioning
confidence: 99%